Clarifications and carnival: Children's embodied investments in a literacy conversation. Issue 2 (4th May 2018) - Laursen, Helle Pia; Kolstrup, Kirsten L.
Abstract: Previous studies of clarification requests in conversations involving second language users typically view such requests as important to obtain 'comprehensible input' or as a form of repair resulting in a sidetrack from the ongoing conversation. This article argues that clarification requests potentially have a much deeper influence on the course of interaction. Using data from a classroom literacy activity, involving three 12 year olds jointly reconstructing a text, the analysis shows how the requests become points of departures for a collective exploration of the symbolic possibilities of sign, text, body and space, through which a Bakhtinian carnivalesque and grotesque universe emerge.